2003
DOI: 10.1016/s0022-328x(03)00765-4
|View full text |Cite
|
Sign up to set email alerts
|

Catalysis of the Michael reaction by iron(III): calculations, mechanistic insights and experimental consequences

Abstract: The Fe III catalysed Michael reaction of b-oxo esters 1 with methyl vinyl ketone (2a) and methyl acrylate (2b) as acceptors is investigated. The proposed mechanism, based on experimental results, is supported for the first time by ab initio calculations. Thereby different Fe III complexes 4, derived from the catalyst and 1, with either neutral (H 2 O) or anionic (a second diketonate 1) coligands are considered and their stabilities calculated. Ligand exchange in 4 by acceptors 2 gives intermediates 5 and subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 21 publications
4
44
0
Order By: Relevance
“…6H 2 O. 65 The reaction is first-order in iron, which is compatible with a one-center template reaction. The authors suggested simultaneous coordination of iron with the enolate and the carbonyl group of the electrophile.…”
Section: Issn 1424-6376mentioning
confidence: 73%
“…6H 2 O. 65 The reaction is first-order in iron, which is compatible with a one-center template reaction. The authors suggested simultaneous coordination of iron with the enolate and the carbonyl group of the electrophile.…”
Section: Issn 1424-6376mentioning
confidence: 73%
“…[2][3][4][5][6][7] Furthermore, kinetic investigations and a suitable choice of substrates have provided evidence that corroborates the proposed mechanism of a one-center template reaction, in which the iron is assumed to act as a Lewis acidic center to facilitate both deprotonation of the coordinated dicarbonyl compound and coupling by means of template effects (Scheme 1). [8] While these mechanistic proposals are in accordance with experimental observations, direct experimental evidence for the active species within the catalytic cycle and the intermediates is lacking so far. However, theoretical investigations support the proposed mechanism and shed light on the effect of the counterion on the reaction rate.…”
Section: Introductionmentioning
confidence: 83%
“…In the first, the catalytically active species possesses no chloride but only water and ester ligands. [8] Therefore, it would be necessary that the chloride ligands present at iron be removed prior to the formation of the active catalyst. In the case of Fe(ClO 4 ) 3 , heterolysis is more facile due to the lower charge density and coordination ability of the counterion.…”
Section: Concentration Effectmentioning
confidence: 99%
See 2 more Smart Citations